A Short Review of Techniques for Phenol Removal from Wastewater - Villegas, Laura G. Cordova; Mashhadi, Neda; Chen, Miao; Mukherjee, Debjani; Taylor, Keith E.; Biswas, Nihar (Current pollution reports, 2016)
Phenolic compounds are priority pollutants with high toxicity even at low concentrations. In this review, the efficiency of both conventional and advanced treatment methods is discussed. The applicability of these treatments with phenol and some common derivatives is compared. Conventional treatments such as distillation, absorption, extraction, chemical oxidation, and electrochemical oxidation show high efficiencies with various phenolic compounds, while advanced treatments such as Fenton processes, ozonation, wet air oxidation, and photochemical treatment use less chemicals compared to the conventional ones but have high energy costs. Compared to physico-chemical treatment, biological treatment is environmentally friendly and energy saving, but it cannot treat high concentration pollutants. Enzymatic treatment has proven to be the best way to treat various phenolic compounds under mild conditions with different enzymes such as peroxidases, laccases, and tyrosinases. This review covers papers from 2013 through January 2016.